1987
DOI: 10.1007/bf01717829
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin I converting enzyme in cerebrospinal fluid of patients with neurological diseases

Abstract: The angiotensin I converting enzyme activity (kininase II, EC 3.4.15.1) was measured fluorimetrically in cerebrospinal fluid (CACE) of 154 patients with neurological disorders and 27 controls. The concentrations of total protein, albumin, and immunoglobulins G and A were also determined. There was no correlation between CACE and sex or age, but a slight positive relation between CACE and total protein and an inverse correlation between CACE and albumin were observed. Compared to controls, significantly elevate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0
3

Year Published

1992
1992
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 17 publications
0
20
0
3
Order By: Relevance
“…To date, several reports have described significantly increased ACE activity in cerebrospinal fluid and serum among patients with MS (Constantinescu, Goodman, Grossman, Mannon, & Cohen, 1997; Kawajiri et al., 2008; Schweisfurth, Schiöberg‐Schiegnitz, Kuhn, & Parusel, 1987). Furthermore, in our previous work with MS patients from Croatian and Slovenian populations, we demonstrated that the homozygous ACE‐DD genotype might contribute to an elevated MS risk among male patients (Lovrečić et al., 2006).…”
Section: Introductionmentioning
confidence: 99%
“…To date, several reports have described significantly increased ACE activity in cerebrospinal fluid and serum among patients with MS (Constantinescu, Goodman, Grossman, Mannon, & Cohen, 1997; Kawajiri et al., 2008; Schweisfurth, Schiöberg‐Schiegnitz, Kuhn, & Parusel, 1987). Furthermore, in our previous work with MS patients from Croatian and Slovenian populations, we demonstrated that the homozygous ACE‐DD genotype might contribute to an elevated MS risk among male patients (Lovrečić et al., 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, increases in the concentration of ACE (ref. 26,27,[33][34][35][36][37] ), IgG-index [38][39][40] , oligoclonal bands 38,39,41 , CD4/CD8 lymphocyte ratios 42 , lysosymes and beta 2-microglobulin concentrations 43 in CSF have been reported. Most studies report evidence of intrathecal synthesis of immunoglobulins with oligoclonal bands in about 30-40% of patients with NS (ref.…”
mentioning
confidence: 99%
“…They compared the CSF ACE levels of 11 patients with ‘probable’ neurosarcoidosis with 207 normal controls, using a radioassay. Schweisfurth et al [18]and Oksanen et al [19]found elevated levels of ACE in CSF in patients with untreated neurosarcoidosis compared with normal controls. They assumed ACE-producing granulomas to be the source.…”
Section: Discussionmentioning
confidence: 99%